Antifouling PEG Coatings by Thiol‐Acrylate Conjugate Addition Reactions for Generation of Protein Patterns via Photobleaching‐Induced Protein Binding (PiPB) BioBitmaps Using Maskless Projection Lithography - Ali Usama; Evelin Schäfer; Pang Zhu; Qingchuan Song; Alexander Weißbach; Dorothea Helmer; Joachim Wollschläger; Changjiang You; Martin Steinhart; Pegah Pezeshkpour; Peilong Hou; Bastian E. Rapp (Advanced Materials Interfaces, 2025)
Abstract Photobleaching‐induced protein binding (PiPB) is a light‐based molecular patterning technique that is introduced as Protein Bitmaps. This technique has significant applications in immunoassays and cell‐substrate interactions. However, commonly used active surfaces, bovine serum albumin (BSA) coatings prepared via physical adsorption, are prone to desorption or displacement by biomolecules with higher substrate affinities, limiting their stability under complex conditions over several days. To address this, covalently bound high‐density antifouling polyethylene glycol (PEG) monolayers are developed by solvent‐free coupling of cost‐effective homo‐bifunctional PEGs (acrylate‐PEG‐acrylate, PEGDA) to glass/glass‐type surfaces silanized with (3‐mercaptopropyl) trimethoxysilane (MPTMS) using thiol‐acrylate conjugate addition reactions at room temperature, resulting in stable antifouling PEGDA surfaces with terminal‐acrylates as free radical acceptors for PiPB. Non‐specific protein binding on PEGDA‐modified surfaces is evaluated using reflectometric interference spectroscopy (RIfS), showing superior antifouling performance compared to BSA‐coated surfaces against avidin and comparable performance against streptavidin and BSA. Furthermore, PiPB with fluorescein‐5‐biotin conjugate (F5B) is carried out on PEGDA‐modified surfaces, performed using a custom‐built digital mirror device (DMD)‐based lithography system, confirming the suitability of PEGDA‐modified surfaces for biomolecule immobilization. The method presented for PEGDA coating preparation has the potential to broaden the applicability of PiPB, particularly using DMD‐based devices, in biomedical and surface engineering fields.